A review of the Afrotropical genus Kenyacus (Coleoptera: Carabidae: Harpalini) from the Rwenzori Mountains, with description of seven new species - Kataev, Boris M. (Zootaxa, 2019)
A taxonomic review of the Afrotropical genus Kenyacus Alluaud, 1917 from the Rwenzori Mountains is given. Tropicoritus Alluaud, 1917 is treated as a new synonym of Kenyacus. Seven new species are described from the eastern part of the Rwenzori Mountains National Park (Uganda): K. gusarovi sp. n., K. parvus sp. n., K. berndi sp. n., K. trechoides sp. n., K. angustatus sp. n., K. similis sp. n. and K. pusillus sp. n. Two species previously known from the Rwenzori Mountains, K. ruwenzorii (Alluaud, 1917) and K. ruwenzoricus Basilewsky, 1955, are re-described, and a key to all described species of Kenyacus from these mountains is provided. The taxonomic position of Kenyacus within the subtribe Stenolophina is discussed. The genus Kenyacus is considered as a member of the Acupalpi genus group and closely related to the genus Anthracus sensu Jaeger, 2012.